EDUCATION AND DEVELOPMENT OF PHYSICAL QUALITIES OF YOUNG VOLLEYBALL PLAYERS THROUGH ACTIVE GAMES (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2023)
A characteristic feature of modern sports is the high level of preparedness of teams and the exceptional preparedness of athletes, as a result of this, an ever-increasing density of sports results. With a high density of results and an increase in sports competition, it is predominantly the one who immediately and correctly assesses, quickly makes an expedient decision, and then effectively implements them in the course of sports wrestling. With an increase in the level of sports results, physical fitness and tactical skills of athletes become more important. Physical training is a necessary basis for young volleyball players. Games, the duration of which is sometimes 2-2.5 hours, place high demands on the versatile preparedness of the athlete, the development of his motor qualities and functional capabilities. Moreover, it is possible to master the majority of volleyball techniques (offensive strike, blocking, fast movements, acrobatic throws and rolls) only if the level of development of physical qualities is quite high.